The German worker : working-class autobiographies from the age of industrialization - Kelly, Alfred, 1947- (University of California Press, 1987)
In the two generations before World War I, Germany emerged as Europe's foremost industrial power. The basic facts of increasing industrial output, lengthening railroad lines, urbanization, and rising exports are well known. Behind those facts, in the historical shadows, stand millions of anonymous men and women: the workers who actually put down the railroad ties, hacked out the coal, sewed the shirt collars, printed the books, or carried the bricks that made Germany a great nation. This book contains translated selections from the autobiographies of nineteen of those now-forgotten millions. The thirteen men and six women who speak from these pages afford an intimate firsthand look at how massive social and economic changes are reflected on a personal level in the everyday lives of workers. Although some of these autobiographies are familiar to specialists in German labor history, they are virtually unknown and inaccessible to the broader audience they deserve. This book provides translations that are at once useful, interesting, and entertaining to a wide range of historians, students, and general readers.